Cocaine: from coca fields to the streets - Arias, Enrique Desmond; Grisaffi, Thomas (Duke University Press, 2021)
Introduction: The moral economy of the cocaine trade / Enrique Desmond Arias and Thomas Grisaffi -- The white factory : coca, cocaine, and informal governance in the Chapare, Bolivia / Thomas Grisaffi -- Tracing cocaine supply chains from within : illicit flows, armed conflict, and the moral economy of Andean borderlands / Annette Idler -- Drug crops, twisted motorcycles, and cultural loss in indigenous Colombia / Autumn Zellers-León -- From Corumbá to Rio : an ethnography of trafficking / Robert Gay -- Border, ghetto, prison : cocaine and social orders in Guatemala / Anthony W. Fontes -- Drug cartels, from political to criminal intermediation : The Caballeros Templarios' mirror sovereignty in Michoacán, Mexico / Romain Le Cour Grandmaison -- Of drugs, tortillas, and real estate : on the tangible and intangible benefits of drug dealing in Nicaragua / Dennis Rodgers -- "A very well-established culture" : cocaine market self-regulation as alternative governance in San Juan, Puerto Rico / Lilian Bobea and Cyrus Veeser -- Visible and invisible "cracklands" in Brazil : moral drug commerce and the production of space in São Paulo and Rio de Janeiro (1990-2017) / Taniele Rui -- The violence of the American dream in segregated US inner-city narcotics markets / Philippe Bourgois, Laurie Kain Hart, George Karandinos, and Fernando Montero -- Shifting south : cocaine's historical present and the changing politics of drug war, 1975-2015 / Paul Gootenberg -- Conclusion. Responding to cocaine's moral economies / Enrique Desmond Arias.